1984
DOI: 10.1111/j.1440-1681.1984.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Reflex Effects of Arterial Baroreceptors and Cardiac Receptors on the Heart Rate of Conscious Rabbits

Abstract: The reflex effects on heart rate (HR) of presumptive cardiac receptors have been differentiated from those of the arterial baroreceptors in conscious rabbits by inflating cuffs on the ascending aorta, descending aorta, inferior vena cava and pulmonary artery. When the outflow from the right ventricle was progressively impeded the accompanying increase in HR was entirely explicable by unloading of the arterial baroreceptors. As the outflow from the left ventricle was progressively impeded there was an initial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…This is because there is functional redundancy among the baroreceptor population, at any rate with respect to the retlex control of blood pressure, which is reflected in the demonstration that interaction among the inputs from the different sets of baroreceptors is usually inhibitory (Spyer, 1981;Abboud and Thames, 1984). In this connection it is noteworthy that the resting levels of blood pressure and heart rate in our rabbits (Table 1), in which only the baroreceptors in one carotid sinus were intact, were very similar to those found in normal rabbits of the same strain with all baroreceptors intact (Blombery and Korner, 1979;Dorward et ai, 1982;Ludbrook, 1984). It is also noteworthy that after 7 days the blood pressure and heart rate were elevated by 24 mmHg and 42 beats min ' respectively (Table 1), values that are very similar to those reported 6 to 7 days after surgical denervation of all baroreceptors (Blombery and Korner, 1979;Ludbrook, 1984).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This is because there is functional redundancy among the baroreceptor population, at any rate with respect to the retlex control of blood pressure, which is reflected in the demonstration that interaction among the inputs from the different sets of baroreceptors is usually inhibitory (Spyer, 1981;Abboud and Thames, 1984). In this connection it is noteworthy that the resting levels of blood pressure and heart rate in our rabbits (Table 1), in which only the baroreceptors in one carotid sinus were intact, were very similar to those found in normal rabbits of the same strain with all baroreceptors intact (Blombery and Korner, 1979;Dorward et ai, 1982;Ludbrook, 1984). It is also noteworthy that after 7 days the blood pressure and heart rate were elevated by 24 mmHg and 42 beats min ' respectively (Table 1), values that are very similar to those reported 6 to 7 days after surgical denervation of all baroreceptors (Blombery and Korner, 1979;Ludbrook, 1984).…”
Section: Discussionmentioning
confidence: 68%
“…The abrupt rise of blood pressure that followed carotid sinus denervation might be expected to excite other cardiovascular receptors, especially those in the left side of the heart (Thoren, 1979). Indeed, the rise of blood pressure exceeds the threshold in conscious rabbits for a heart rate depressor reflex that originates from vagally innervated left-sided cardiac receptors (Ludbrook, 1984), but this is a reflex that acts powerfully within seconds. It has been suggested that a rise of blood pressure increases the renal excretion of water and sodium, and so reduces blood volume (Guyton et ai, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive increases in MAP caused reflex bradycardic responses that lay obviously below the level of the lower plateau of the fitted baroreceptorheart rate reflex curve (barocurve). These points were removed as outliers, indicative of cardiac reflex activation and not a component of the baroreceptor reflex (Ludbrook, 1984).…”
Section: Haemodynamicsmentioning
confidence: 99%
“…Baroreceptor-heart rate reflex This was elicited by inflating the aortic and caval cuffs so that MAP rose or fell at 1-2 mmHg s 1 (Ludbrook, 1984).…”
Section: Simulated Haemorrhagementioning
confidence: 99%
“…At first, peripheral resistance increases along with the fall of cardiac output, so that mean arterial pressure is maintained at a near-normal level (Ludbrook & Graham, 1984;Schadt et al, 1984;Ludbrook & Rutter, 1988;Ludbrook et 1 Author for correspondence. al., 1988).…”
Section: Introductionmentioning
confidence: 99%